(untitled) (CIPEEX, 2026)
Introduction: The COVID-19 pandemic, declared in March 2020, significantly impacted health systems worldwide, disrupting prevention and treatment services for various conditions, including HIV. Despite advances in public policies, HIV remains a major public health challenge in Brazil, with marked regional and social inequalities.Objective: To describe and compare the clinical and epidemiological characteristics of HIV cases in Anápolis during the post-pandemic period (2023–2024).Methods: This is an observational analysis based on data from DATASUS/SINAN. Individuals diagnosed with HIV between January 2023 and December 2024 (n = 64) were included.Results: Anápolis recorded 541 HIV cases, with 233 in 2023 and 308 in 2024, showing a significant increase. Most cases occurred among men and young adults aged 22 to 27 years, indicating that this group is the most vulnerable. Among women, six pregnant cases were reported. A higher concentration of cases was observed in the downtown area, followed by Jundiaí, while Boa Vista, Vila Jaiara, and Cidade Universitária formed a second group with elevated frequency.Conclusion: The HIV epidemic in Anápolis remains concentrated among young male and mixed-race adults, reinforcing well-known social inequalities. Although progress has been made, such as the absence of vertical transmission, significant gaps persist in the quality of epidemiological records, particularly in clinical variables.